Peasant Divorces in Documents of Tobolsk Ecclesiastical Consistory of 19th — Early 20th Centuries - A. V. Spichak (Научный диалог)
Peculiarities of paperwork of the Tobolsk ecclesiastical consistory in cases of divorce of peasants due to adultery of their wives in the second half of the 19th — early 20th centuries are considered. Documents stored in the State Archives in Tobolsk testify to the presence of a number of stages of office work on each issue. The basic requirements for the commencement of proceedings in cases of divorce due to adultery (treason) are determined. The obstacles on the way to divorce among peasants in the second half of the 19th — early 20th centuries are established. The author divided them into two groups: errors in the provision of a package of documents and shortcomings in record keeping in the Tobolsk province. The relevance of the study is due to the existence of currently acute social problems caused by a large number of family breakups, the main of which is population decline. Referring to the history of divorce proceedings and the methods used to reconcile spouses (admonition by parish priests) can be useful for rethinking the methods of resolving and preventing marital conflicts, as well as for revealing certain aspects of the history of office work of institutions.